2014
DOI: 10.1074/jbc.m114.556290
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14-3-3β Gene as a Novel miR-152 Target Using a Proteome-based Approach

Abstract: Background: miR-152 regulates HLA-G and HLA-C, which act inhibitory to NK and T cells, thereby altering the immunogenicity of tumors. Results: Applying a proteome-based approach, novel miR-152 targets were identified, e.g. anti-apoptotic 14-3-3␤ overexpressed in certain tumors. Conclusion:The known tumor-suppressive miR-152 regulates 14-3-3␤, thereby enhancing the sensitivity of tumor cells for apoptosis. Significance: miR-152 exerts a dual role by altering the immunogenicity and the tumorigenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Whereas differentially expressed proteins were classified by a fold change ratio of 1.5 (increased or decreased) and a p-value of < 0.05, mass spectrometry analyses were performed on an ultrafleXtreme™ matrix-assisted laser desorption/ionization time of flight mass (MALDI-TOF) mass spectrometer (Bruker Daltonics Inc., Bremen, Germany). The resulting peptide mass fingerprinting datasets were analyzed using the MASCOT software package (Matrix Science, Dauheim, USA) [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas differentially expressed proteins were classified by a fold change ratio of 1.5 (increased or decreased) and a p-value of < 0.05, mass spectrometry analyses were performed on an ultrafleXtreme™ matrix-assisted laser desorption/ionization time of flight mass (MALDI-TOF) mass spectrometer (Bruker Daltonics Inc., Bremen, Germany). The resulting peptide mass fingerprinting datasets were analyzed using the MASCOT software package (Matrix Science, Dauheim, USA) [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In cancer cells, the increased HLA-G expression is closely correlated with the loss of some HLA-Gtargeting miRNAs. Specifically, several members of miR-148 family such as miR-148a, miR-148b, and miR-152 could downregulate HLA-G expression [65][66][67]. In breast cancer cells, it was observed that oncogenic estrogenic G-protein-coupled estrogen receptor-1 (GPER) signaling pathway decreased downstream miR-148a level, further contributing to cancer immune evasion [68].…”
Section: Hla-g-targeting Mirnasmentioning
confidence: 99%
“…55 NIH/3T3 cells were stably transfected with the miR and/or the HLA-G expression vectors using the Effectene Transfection Reagent (Qiagen, Cat. no.…”
Section: Generation Of Hla-g and Mir Expression Vectors And Cell Tranmentioning
confidence: 99%